Measuring Set Latent Variables Through Exploratory Factor Analysis with Principal Components Extraction and Validation with AMOS Software (European Journal of Pure and Applied Mathematics, 2017)
The aim of this paper is to show a path to measure a set latent variable through exploratory factorial analysis and confirmatory analysis. It starts with the theoretical mathematical procedure and then, with a database, it shows the re-specified model of study. For data analysis SPSS v.23 and AMOS v.23 statistic software are used.
Keywords: Factor analysis; confirmatory analysis; structural equations; factorial weights; communalities; variance